You never transition alone! Exploring the experiences of youth with chronic health conditions, parents and healthcare providers on self‐management. (22nd April 2016) - Nguyen, T.; Henderson, D.; Stewart, D.; Hlyva, O.; Punthakee, Z.; Gorter, J. W.
Abstract: Background: Recent evidence suggests that fostering strategies to enable youth with chronic health conditions to work towards gradual self‐management of their health is key in successful transition to adult healthcare. To date, there is limited research on self‐management promotion for youth. The purpose of this study is to explore self‐management from the perspectives of youth, parents and healthcare providers in transition to adult healthcare. Methods: Part of a larger longitudinal transition (TRACE‐2009–2013) study, interpretive phenomenology was used to explore the meaning of the lived experiences and perceptions of youth, parents, and healthcare providers about transition to adult healthcare. Purposeful sampling was utilized to select youth with a range of chronic health conditions from the TRACE cohort (spanning 20 diagnoses including developmental disabilities and chronic conditions), their parents and healthcare providers. Results: The emerging three themes were: increasing independence of youth; parents as safety nets and healthcare providers as enablers and collaborators. The findings indicate that the experiences of transitioning youth, parents and service providers are interconnected and interdependent. Conclusions: Results support a dynamic and developmentally appropriate approach when working with transitioning youth and parents in practice. As youth depend on parents and healthcare providers for support in taking charge of their own health, parents and healthcare providers must work together to enable youth for self‐management. At a policy level, adequate funding, institutional support and accreditation incentives are recommended to allow for designated time for healthcare providers to foster self‐management skills in transitioning youth and parents.